A native mass spectrometry platform identifies HOP inhibitors that modulate the HSP90–HOP protein–protein interaction. Issue 83 (30th September 2021) - Veale, Clinton G. L.; Mateos-Jiménez, Maria; Vaaltyn, Michaelone C.; Müller, Ronel; Makhubu, Matodzi P.; Alhassan, Mahama; de la Torre, Beatriz G.; Albericio, Fernando; Mackay, C. Logan; Edkins, Adrienne L.; Clarke, David J.
Abstract : We demonstrate the potential of native mass spectrometry for modelling Protein–Protein Interactions, leading to the identification of inhibitors of the HSP90–HOP PPI. Abstract : Herein we describe a native mass spectromery protein–peptide model as a competent surrogate for the HOP–HSP90 protein–protein interaction (PPI), application of which led to the qualititive identification of two new peptides capable of in vitro PPI disruption. This proof of concept study offers a viable alternative for PPI inhibitor screening.